Дослідження роменсько-давньоруських пам’яток на шляху із Чернігова у Тмуторокань - Приймак, В.В. (Археологія, 2006)
Опубліковано результати багаторічних польових досліджень населених пунктів на шляху із Чернігова у Тмутаракань (шевченківського, зеленогайського, шпилевського, заріченського археологічного комплексів). В статье подводятся итоги многолетних полевых исследований населенных пунктов на пути из Чернигова в
Тмутаракань: шевченковского, зеленогайского, шпилевского, заречненского археологических комплексов.
Публикуются наиболее интересные материалы исследований зеленогайского комплекса в 2004 г. Аргументируется усиленное развитие зернового хозяйства в населенных пунктах на международных путях, обусловленное потребностями обеспечения караванов и возможностью экспорта зерна. Время наибольшей интенсивности
функционирования пути Чернигов — Тмутаракань приходится на ХІ–ХІІ вв. The article sums up multi-year field research of settlements located on the path leading from Chernihiv to Tmutarakan:
Shevchenkivskyj Zelenohaiskyj, Shpilevskyj, Zarechnenskyj archaeological complexes. The most interesting materials
from the Zelenohaiskyj complex studied in 2004 are published here. Arguments are advanced in favor of intensive
development of grain farming in settlements located on international routes, what resulted from the necessity to provide
the supplies for the caravans and the possibility of grain export. The Chernihiv - Tmutarakan route was most intensively
used in the ХІ – ХІІ cc.